Association between transferred embryos and multiple pregnancy/live birth rate in frozen embryo transfer cycles: A retrospective study - Wu, Xian; Zhou, Wen-jie; Xu, Bu-fang; Chen, Qian; Xia, Lan; Zhao, Shen; Xu, Hui-hui; Zhang, Ai-jun; Niu, Zhi-hong (Frontiers in Endocrinology, 2023)
Background: Physicians need an appropriate embryo transfer strategy to address the challenge of reducing multiple birth rates, while maintaining the couples’ live birth rate during assisted reproductive technology. Methods: We included 10,060 frozen embryo transfer cycles from January 2015 to March 2020 in reproductive medical center of Ruijin hospital, Shanghai, China. Patients were grouped according to the number and grade of cleavage-stage embryo or blastocysts transferred. Live birth rate and multiple live birth rate were compared among groups of women of different ages. Multivariable logistic regression models were used to estimate the risk of multiple live birth using different combinations of transferred embryos. Results: The transfer of double good-quality embryos was an independent predictor for multiple birth in women aged <30 years and those aged 36‒39 years [<30 years: aOR =1.54 (95% CI: 1.14‒2.06, P < 0.01); 36‒39 years: aOR =1.84 (95% CI: 1.0‒3.4, P < 0.01)]. Further, for women aged <36 years, the transfer of good-quality + poor-quality blastocysts was an independent predictor for multiple birth rate [<30 years: aOR=2.46 (95% CI: 1.45‒4.18, P < 0.01); 31‒35 years: aOR =4.45 (95% CI: 1.97‒10.06, P < 0.01)]. Conclusions: Single-good-quality blastocyst transfer is recommended for women of all ages. When good-quality cleavage embryos are available, the choice of single or double embryo transfer with good- or average-quality embryo should depend on the age of women. Double embryo transfer with the highest possible grade of embryos is recommended for women aged ≥40 years.